2015
DOI: 10.1007/s00259-015-3246-8
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI and PET/CT: is there room for both at the top of the food chain?

Abstract: In this issue of the journal, Vrachimis and colleagues demonstrate that positron emission tomography combined with Xray computed tomography (PET/CT) outperforms PET combined with magnetic resonance imaging (PET/MRI) in restaging radioiodine-negative patients with biochemical relapse of differentiated thyroid carcinoma [1]. This comes as a surprise, at least to the uninitiated: In a world predominantly driven by material considerations, common sense would presume that diagnostic accuracy correlates with costs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Si nce the introduction of clinical PET/MRI in 2010, much of the research into this modality has focused on diagnostic performance. However, comparative studies to date have largely shown equivalent diagnostic capabilities for these modalities (1,2). Where benefits for PET/MRI have been demonstrated, they are typically small or apply to relatively small populations of patients.…”
mentioning
confidence: 99%
“…Si nce the introduction of clinical PET/MRI in 2010, much of the research into this modality has focused on diagnostic performance. However, comparative studies to date have largely shown equivalent diagnostic capabilities for these modalities (1,2). Where benefits for PET/MRI have been demonstrated, they are typically small or apply to relatively small populations of patients.…”
mentioning
confidence: 99%